Gold price prediction using radial basis function neural network - Hussein, S. F. M. (IEEE Explorer, 2011)
Gold is a precious metal once widely used as a standard for monetary exchange but was replaced by paper currency mostly used today. However interest in gold trading and investment has resurfaced recently in Malaysia probably due to its price stability. Samples of gold that are used as investment include the Kijang Emas, Public Dinar and the Public Gold which are currently available to the general public in Malaysia. This project will involve developing a system to aid a gold investor in deciding the best time in the future to buy or sell gold. The system developed is based on existing gold data time series and algorithms based on Artificial Neural Networks. The system should be able to give daily prediction to its users.